The Influence of the Teaching Factory Learning Model on Entrepreneurial Interest and Readiness Entrepreneurship Students of Hasanah Vocational School, Pekanbaru - Safitri, Yolani; Caska, Caska; Dedi Irawan (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze and examine the influence of the teaching factory learning model on students' entrepreneurial interest and entrepreneurial readiness. This study uses a quantitative descriptive approach with a population of all students majoring in Financial Accounting, Film, Motorcycle Business Techniques at SMK Hasanah Pekanbaru with a population of 143 students and a sample in this study of 106 students. While the sampling technique uses random sampling. Data were collected by questionnaire and documentation with data analysis techniques using Structural Equation Modeling (SEM) Partial Least Square (PLS) . The results of the study show that the teaching factory learning model has an effect on entrepreneurial readiness. This means that the better the implementation of the teaching factory learning model is carried out and students also follow it well so that they have a lot of experience, it will have an impact on their entrepreneurial readiness, such as being physically and mentally ready to open a business. Furthermore, the teaching factory learning model also has an effect on entrepreneurial interest, and entrepreneurial interest has an effect on entrepreneurial readiness, meaning that if someone has a strong drive in entrepreneurship, they will tend to form good entrepreneurial readiness. such as the emergence of high self-confidence and the ability to take risks.